Evaluation of the performance and stability of early maturing orange-fleshed sweetpotato genotypes in selected areas in Ethiopia. - Bililign Mekonnen; Fekadu Gurmu (PLoS ONE)
Orange-fleshed sweetpotato varieties that mature and harvest sooner play an important role in addressing food and nutrition demands in areas where irregular rainfall makes sustainable production challenging. A national variety trial was conducted in 2021 and 2022 during the main cropping season using ten OFSP genotypes in three locations in Sidama, South, and Oromia regions of Ethiopia, namely Hawassa, Arbaminch, and Koka, respectively. The objective of this study was to develop and select early-maturing and high-yielding OFSP genotypes for short-term harvesting (3-4 months). The field trial was conducted in a randomized complete block design with three replications. Data were collected on root yield and yield-related traits, sweetpotato virus disease reactions (SPVD), root dry matter (DMC), and beta-carotene contents (BCC) and were subjected to analysis of variance. A genotype plus genotype by environment interaction (GGE) bi-plot was also used to determine genotype stability. The results showed the presence of highly significant (p<0.001) differences among locations and genotypes, reflecting the existence of differential responses among genotypes in varied locations. Based on combined analysis, G3 (13NC9350A-9-3) outperformed the other genotypes for most of the traits considered, except for DMC, i.e., which has an equivalent to the check variety (Alamura) and showed a yield advantage of 41.4% over it. The GGE biplot also revealed that the G3 was the vertex genotype with the consistent performance in all environments. It had a low score of 1.39 on the 1-9 scoring scale, indicating that it falls within the resistant range, with adequate levels of BCC (5.5 mg/100 g) and DMC (30.0%). Furthermore, G3 is an early-maturing variety, which allows other crops to be grown in double and relay cropping systems. Therefore, based on its outstanding performance, G3 is recommended for verification and release for cultivation in mid- to low-land areas in Ethiopia.